PERAN GURU PENDIDIKAN AGAMA KRISTEN DALAM MENGEMBANGKAN KECERDASAN SPIRITUAL ANAK DITINJAU DARI ROMA 12:2 - Katji Mariany Naat (THEOSOPHIA: Jurnal Teologi dan Pendidikan Kristiani, 2025)
Christian Education Teachers (PAK) play a strategic role in developing children's spiritual intelligence, as spiritual education not only emphasizes cognitive aspects but also the formation of character and foundational faith values. Romans 12:2 highlights the importance of the renewal of the mind as the basis for life transformation, enabling children not to conform to worldly patterns but to live according to God’s will. This verse provides a theological foundation indicating that the development of spiritual intelligence should focus on transforming children’s thinking and behavior in alignment with Christian values. This study aims to describe the role of PAK teachers in fostering children’s spiritual intelligence from a biblical perspective, particularly Romans 12:2. A qualitative descriptive method was employed, using literature review, interviews, and classroom observation. The findings indicate that PAK teachers act as role models, spiritual guides, motivators, and facilitators in instilling faith values, developing spiritual habits, and accompanying children in facing life challenges. Through consistent guidance, children are able to cultivate spiritual intelligence rooted in mind renewal, discern God’s will, and live according to Christian principles. These findings underscore the critical role of PAK teachers in holistically guiding children’s spiritual transformation.